Efeito de herbicidas no desenvolvimento inicial de variedades de cana-de-açúcar e no controle de plantas daninhas - Sabbag, Renan dos Santos (2015)
The chemical method of weed control is the most used in the culture of sugarcane, and studies covering not only the management of plants, but also the effect of these herbicides on crop development, especially in new varieties. Therefore, this study was conducted with the objectives: (1) evaluate the effectiveness of control of ametryne herbicides, clomazone, diuron + hexazinone, metribuzin, saflufenacil, sulfentrazone and tebuthiuron used in isolation and in combination, in controlling Ipomoea nil, Ipomoea triloba and Merremia cissoides, submitted to different periods of drought, with 0, 20, 40 and 60 days without irrigation; (2) evaluate the effect of ametryne herbicides, clomazone, diuron + hexazinone, metribuzin, saflufenacil, sulfentrazone and tebuthiuron in the early development of varieties of sugarcane through pre-sprouted seedlings. The tests were conducted in a greenhouse in the CCA / UFSCar with controlled irrigation sprinkler. 4-liter pots were used, filled with sandy clay loam soil. The experimental design was completely randomized with four repetitions, in both parts of the project. At work on effectiveness of herbicides in weed control, herbicides were applied on the ground and subjected to drought periods of 0, 20, 40 and 60 days before sowing the weed species. After the drought 0, 20 40 and 60 days, the seeds of Ipomoea nil, Ipomoea triloba and Merremia cissoides were sown with minimal soil disturbance and evaluations were made 45 days after sowing (DAS), visually We used a percentage scale. In working with seedlings of sugarcane varieties, herbicides were applied at 3 and 10 days after transplantation of pre-sprouted seedlings and were made visual assessments with 7, 15, 30 and 60 days after treatments (DAT), also using a visual scale ranging from 0 to 100%. In quantitative assessments we evaluated the plant height parameters (m), leaf area (cm2) and shoot dry biomass (g) with 60 DAT. With respect to efficiency in weed control there was a reduction of saflufenacil herbicides control efficiency, clomazone, ametryne and metribuzim when subjected to drought periods. In the case of saflufenacil control efficacy was maintained until 20 days of drought. The varieties of pre-sprouted seedlings (BPMs) were shown to be different in phytotoxicity and biometric parameters in relation to the applied herbicide. The treatment saflufenacil + clomazone is phytotoxic to as sugarcane cuttings, however, depending on the variety, did not affect its dry biomass. The metribuzin, was the most selective herbicide in association with saflufenacil, saflufenacil isolated showed phytotoxicity below 30% in all varieties.